2012
DOI: 10.7314/apjcp.2012.13.8.4125
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of 498 Primary Soft Tissue Sarcomas in a Single Turkish Centre

Abstract: Background: Soft tissue sarcomas (STS) must be managed with a team involving pathologists, radiologists, surgeons, radiation therapists and medical oncologists. Treatment modalities and demographic charasteristics of Turkish STS were analysed in the current study. Material-Methods: Primary adult STS followed between 1999-2010 in Cukurova University Medical Faculty Department of Medical Oncology were analzied retrospectively Results: Of the total of 498 patients, 238 were male and 260 female. The most seen adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Meanwhile, resectability has emerged as an important prognostic factor in thoracic STS, as well as all other types of STS. 28 Other prognostic factors, such as tumor grade, diameter, and stage were similar to those detected in previous large STS series. 2 , 4 , 20 , 21 , 26 However, among patients with resectable tumors, thoracic STS patients might have better prognostic characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, resectability has emerged as an important prognostic factor in thoracic STS, as well as all other types of STS. 28 Other prognostic factors, such as tumor grade, diameter, and stage were similar to those detected in previous large STS series. 2 , 4 , 20 , 21 , 26 However, among patients with resectable tumors, thoracic STS patients might have better prognostic characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…Endostar combined with chemotherapy resulted in a higher disease control rate and longer progression-free survival (Zhang et al, 2013). In the study of Asia-Pacific region, specialists suggest RPLS be multi-disciplinarily managed with a team involving pathologists, radiologists, surgeons, radiation therapists and medical oncologists because of the different histotypes, sites, and disease stages assessed (Duman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When we searched the literature on this issue, we could not obtain precise data on the prognostic value of uterine localization of the tumor in patients with STS. In a retrospective of patients with STS, it was reported that there was no relationship between localization of the tumor and survival 20 . However, leiomyosarcoma is the most common histological subtype of STS located at the uterus, and it has been reported that patients receiving pazopanib for leiomyosarcoma have better results than the patients with other histological subtypes in terms of PFS and OS 19 .…”
Section: Discussionmentioning
confidence: 99%